2013
DOI: 10.1177/0748233713511513
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of folic acid on experimental diabetic peripheral neuropathy

Abstract: Diabetic peripheral neuropathy (DPN) is widely considered as a degenerative complication of diabetic patients. The clinical effectiveness of folic acid (FA) on DPN is uncertain. The objective of the present study was to determine the effect of FA in DPN using electromyography (EMG), histopathological examination, immunohistochemistry, inclined plane test, and malondialdehyde (MDA) levels as a marker for lipid peroxidation in experimental diabetic rats. A total of 21 Sprague Dawley rats were randomly divided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 28 publications
2
20
0
4
Order By: Relevance
“…12 In an experimental model of DPN, folic acid protected against DPN, which was related to neuroprotective effects of folic acid. 17 Research on methylcobalamin (MC), the active form of vitamin B12, found that MC improved the somatic and autonomic symptoms of diabetic neuropathy among DPN patients (without causing side effects), 18 enhanced nerve regeneration in rats with DPN, 19 and delayed onset of DPN in rats. 20 An in vitro study showed that pyridoxine (P), the active form of vitamin B6, along with pyridoxamine (PM) were found to inhibit superoxide radical production, reduce lipid peroxidation and glycosylation, and increase the (Na + + K + )-ATPase activity in high glucose-exposed red blood cells (RBC) -suggesting P or PM supplementation may delay or inhibit DPN.…”
Section: Introductionmentioning
confidence: 99%
“…12 In an experimental model of DPN, folic acid protected against DPN, which was related to neuroprotective effects of folic acid. 17 Research on methylcobalamin (MC), the active form of vitamin B12, found that MC improved the somatic and autonomic symptoms of diabetic neuropathy among DPN patients (without causing side effects), 18 enhanced nerve regeneration in rats with DPN, 19 and delayed onset of DPN in rats. 20 An in vitro study showed that pyridoxine (P), the active form of vitamin B6, along with pyridoxamine (PM) were found to inhibit superoxide radical production, reduce lipid peroxidation and glycosylation, and increase the (Na + + K + )-ATPase activity in high glucose-exposed red blood cells (RBC) -suggesting P or PM supplementation may delay or inhibit DPN.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we observed the lowest g‐ratio in the RF group and there was a significant difference among the RF group and other groups. Previous studies reported that the prolongation in CMAP latency was due to increased myelin sheath thickness caused by edematous swelling, delamination, and rarefaction in the myelin sheath [Cankayali et al, ; Yilmaz et al, ]. We also thought that the decrease in CMAP amplitude was due to the decreased g‐ratio caused by axonal loss and increase of myelin sheath thickness.…”
Section: Discussionmentioning
confidence: 58%
“…Group IV: (DA+FA): Diabetes-induced plus folic acid group; two weeks after the STZ injection, FA was injected intraperitoneally (10 mg/kg/day) for 4 weeks [5].…”
Section: Experimental Designmentioning
confidence: 99%
“…An increase in homocysteine levels or oxidative stress may be one of the possible mechanisms contribute to the development of DPN. A number of studies associated with FA deficiency and increased plasma total homocysteine levels show higher risk of vascular disease, cerebral ischemia, neuropsychiatric and neurodegenerative diseases [5]. Moreover, FA supplementation has been used to support a range of health concerns including DPN and provide neural protection in some neurological diseases [6].…”
Section: Introductionmentioning
confidence: 99%